Characterization of e-waste : rare earth element identification - Muhamad Ariff Shazlan, Roslan (2015)
Rare Earth Element (REE) or rare earth metal is one of a set of seventeen chemical elements in the periodic table. Rare earth element are widely used in many consumer electronics products such as smartphones, led monitor, powerful magnets in electric drive motors and etc. This research describes the study of the coating powder leaching from computer monitor scraps to obtain liquor which can be treated by hydrometallurgical techniques to extract the metals. Television(TV) tubes and computer monitors exist as coating powder that contain some rare earth elements(REEs). The recovery of the REEs from electronics scraps is very important in lieu of the economic and concerns. Leaching is a method of separation between solid and liquid. To separate the components, acid solvents such as nitric acid, hydrochloric acid, and sulphuric acid can be used. The results of this study pointed out the technical viability of the recovery of the metals. The coating powder used in this study was obtained by manually scraping the inner surfaces of computer monitor. Sulphuric (H2SO4), nitric acid (HNO3) and hydrochloric (HCl) acids will be used in the leaching experiments. All solutions are analytical grade reagents and diluted with distilled water. The extract sample will be characterized by X-ray diffractometer. From the X-ray difractometer, the data shows that LCD contain large value of indium. The conclusion that can be made from this study is for leaching process to extract rare earth elements, hydrochloric acid is the best solvent that can be used. Besides, in order to make sure the leaching process is effective, higher molarity of acid solvent is needed